Institutional Performance and Progress at Rawalpindi Medical College & Its Allied Hospitals 2014-16- A SWOT Analysis - Muhammad Umar ,Faiza Aslam , Maliha Gull Tarar, Nadeem Ikram (Journal of Rawalpindi Medical College, 2016)
Background: A SWOT (strengths, weaknesses, opportunities and threats) analysis of institutional performance and progress at Rawalpindi Medical College and its Allied Hospitals during period of 2014-16 was conducted. Methods: This cross sectional study using mixed quantitative and qualitative approach was conducted at Rawalpindi in December 2016 at Rawalpindi Medical College and Rawalpindi Medical College (RMC) and its three Allied Hospitals Data was collected through observation of all available administrative records and also through 30 in depth interviews and 4 Focus group discussions with senior administrative staff members, senior faculty staff members, Post Graduate Trainees of various specialties, nurses and paramedics, inpatients and undergraduates of RMC were carried out. Results: The salient features of progress at RMC & Allied hospitals were provision of new advanced diagnostic and therapeutic equipment, induction of new personnel, initiation of new specialties, commencement of various programs for faculty, post graduate training and academic and extracurricular programs for undergraduates of RMC. Renovation of various buildings at RMC & Allied hospitals also took place while Research capacity was enhanced swiftly. Weaknesses in various areas were also identified in addition to all potential opportunities and threats. Conclusion: The performance and progress at RMC and Allied hospital during period 2014-16 remained significant with few weaknesses too, by overcoming which, it can further strive for unparalleled quality in medical education.